SUPERVISI PENDIDIKAN DALAM PENINGKATAN MUTU PENDIDIKAN DI SEKOLAH - Ariasa Giri, I Made (Jurnal Penjaminan Mutu, 2016)
Supervision isÂ  imperative for the improvement of the school education quality. In doing a supervision the supervisor should pay attention to the process, effectiveness, the system, the information,the evaluation, the principles, the programs, and the objectives, and the clinical model.